Serum haptoglobin concentrations in dogs with liver disease. (14th December 2013) - Crawford, K.; Warman, S. M.; Marques, A. I.; Yool, D. A.; Eckersall, P. D.; McCulloch, E.; Lynn, K.; Mellanby, R. J.; Gow, A. G.
Abstract : Dogs with liver disease have been shown to have increased serum C‐reactive protein (CRP) concentrations. However, it is unclear whether dogs with liver disease also have increased serum haptoglobin concentrations. The aim of the study was to measure serum haptoglobin concentrations in healthy dogs, hospitalised dogs and dogs with liver diseases. Haptoglobin concentrations were measured in 30 healthy dogs, 47 hospitalised dogs with non‐hepatic illness, 46 dogs with congenital portosystemic shunt (cPSS) and 11 dogs with primary hepatopathy. Haptoglobin concentrations were not significantly different between cPSS dogs with and without hepatic encephalopathy (HE), thus all cPSS dogs were considered as one group. Haptoglobin concentrations were significantly different between the remaining groups (P<0.0001). Hospitalised ill dogs had significantly higher haptoglobin concentrations than healthy dogs (P<0.001), dogs with cPSS (P<0.001) and dogs with primary hepatopathy (P<0.05). There was no significant difference between haptoglobin concentrations in healthy dogs, dogs with cPSS and dogs with primary hepatopathy. Haptoglobin concentrations were not significantly increased in dogs with liver diseases or in dogs with cPSS and HE. This is in contrast with the previously reported CRP results. This study demonstrates that liver function should be considered when interpreting haptoglobin concentrations in dogs.